Unusual involvement in mycosis fungoides: Duodenal papilla - Gómez Venegas, Álvaro Andrés; Vargas Rubio, Rómulo Darío (Revista española de enfermedades digestivas, 2016)
Mycosis fungoides (MF) is a type of T-cell lymphoma with cutaneous involvement. It is a rare disease, of low incidence and usually affects middle-aged men. In most cases only the skin is involved although in advanced stages may present with extra cutaneous involvement including the gastrointestinal tract. We report the first case of MF with compromise of duodenal papilla, emphasizing the diagnostic approach and a brief review of the subject. This case report proves the value of the endoscopic studies in patients with lymphoproliferative disorders, because of the impact in the diagnosis and prognosis. Also, this case report is relevant because there is no scientific evidence, as far as we know, of similar cases reported.